Sharing Economy Analysis of Cost Structure and Economies of Scale on Transportation Platforms - Kholilul Kholik; Syaiful Kadri (Sean Institute, 2026)
The sharing economy phenomenon has transformed the conventional transportation industry paradigm through asset digitization and resource allocation efficiency. This study aims to analyze the cost structure and economies of scale mechanism on application-based transportation platforms. Unlike traditional transportation companies that have heavy asset burdens, transportation platforms operate with an asset-light model where the capital costs of vehicle procurement and maintenance are transferred to driver partners. The analysis shows that the platform's cost structure is dominated by high fixed costs for the development of technology infrastructure, algorithms, and marketing, but has very low marginal costs for each additional service transaction. This condition allows for the creation of significant economies of scale; as user volume and network density increase, the average cost per service decreases dramatically. Network effects are the main catalyst in strengthening market position and creating barriers to entry for competitors. The study concluded that long-term profitability on this platform is highly dependent on the company's ability to reach break-even point through massive transaction volumes to cover initial technology investments.